SY 14-3 PRIMARY ALDOSTERONISM IN RESISTANT HYPERTENSION. (September 2016) - Calhoun, David
Abstract : N/A: Resistant hypertension refers to patients with difficult-to-treat hypertension, generally defined as needing three or more medications of different classes, including, if tolerated, a diuretic. 1 Observational studies indicate that the prevalence of resistant hypertension based on the preceding definition of needing 3 or medications for blood pressure (BP) control is approximately 15-20% of patients being treated for hypertension. 2, 3 However, causes of pseudoresistance are common, including poor BP technique, poor adherence, white coat effects, and under-treatment, all of which must be identified in order to distinguish apparent resistance from true treatment resistance. 4-8 Multiple studies indicate that primary aldosteronism is an especially common cause of antihypertensive treatment resistance. Observational studies from different clinics worldwide have demonstrated a prevalence of primary aldosteronism of approximately 20% of patients with confirmed resistant hypertension. 9-12 Additional studies indicate, however, that is 20% is likely an under estimate of the role that hyperaldosteronism plays in contributing to pharmacologic treatment resistance. Studies based on indices of volume status, aldosterone levels, and aldosterone to renin ratio levels, provide evidence of aldosterone-related fluid retention in up to 60-70% of patients with resistant hypertension. 13, 14 The etiology of this degree of aldosterone excess remains obscure, but recent analyses of large cohorts of patients with resistant hypertension specifically indicate a strong positive correlation between increasing body weight and increasing aldosterone levels. 15 This observation suggests that adipocytes may serve as an important source of an aldosterone-stimulating factor contributing to excess aldosterone release in patients with resistant hypertension. The relation between increasing aldosterone levels and increasing body mass index (BMI) is true of both men and women with resistant hypertension, but the positive correlation is considerably stronger for men. Multiple mechanisms may be contributing to this gender difference, but one explanation may be that centrally located or abdominal adipose tissue, more typical of men, is the larger source of this purported aldosterone secretagogue compared to peripheral adipose tissue that is more characteristic of women. Such an effect would be consistent with experimental studies demonstrating that adipocytes release an as of yet unidentified aldosterone-secretagogue that serves as a potent stimulus of aldosterone release from isolated adrenal cells. 16 Elucidation of the role that adipocytes play in contributing to the high prevalence of aldosterone excess that is apparent in patients with resistant hypertension is an important goal of future studies.